1993
DOI: 10.1182/blood.v81.10.2566.bloodjournal81102566
|View full text |Cite
|
Sign up to set email alerts
|

Long-term engraftment of normal and post-5-fluorouracil murine marrow into normal nonmyeloablated mice [see comments]

Abstract: We report the successful long-term engraftment of normal male donor bone marrow (BM) transfused into noncytoablated female mice, challenging the assumption that “niches” need to be created for marrow to engraft. We have used chromosomal banding and Southern blot analysis to identify transplanted male marrow cells, and shown the long-term stability of the chimeric marrows. Balb/C, BDF1, or CBA-J female hosts (no irradiation) received for 5 consecutive days 40 x 10(6) male cells (per day) of the same strain, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 0 publications
6
53
1
Order By: Relevance
“…al. 6 extended these observations showing high levels of long-term multilineage engraftment in nonmyeloablated BALB/c mice. A series of studies utilizing a male/female transplantation model in nonmyeloablated BALB/c hosts has shown that engraftment is essentially quantitative and appears to be determined by competition between infused marrow cells and host cells.…”
supporting
confidence: 56%
“…al. 6 extended these observations showing high levels of long-term multilineage engraftment in nonmyeloablated BALB/c mice. A series of studies utilizing a male/female transplantation model in nonmyeloablated BALB/c hosts has shown that engraftment is essentially quantitative and appears to be determined by competition between infused marrow cells and host cells.…”
supporting
confidence: 56%
“…Previously Micklem, Saxe, Brecher and coworkers had demonstrated variable degrees of normal engraftment [ 1-31. More recently we confirmed and extended these results showing relatively high levels of stable engraftment of male BALB/c cells in nontreated female BALB/c hosts; levels of male DNA of up to 42% in female host marrow were found at 24-25 months after infusion of 40 x lo6 cells for five consecutive days (total 200 x lo6 cells) [4].…”
Section: Introduction and Discussionmentioning
confidence: 99%
“…Therefore, determination of cell division based on dilution of the membrane linkers should be carefully performed. Because some hematopoietic progenitors proliferate early after transplantation [42,44,45], PKH dyes are optimal for short-term tracking of BMCs and for detection of quiescent cells over longer periods.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…A prevalent notion postulates that transplanted cells seek a vacant hematopoietic niche, and thus, the success of engraftment reflects a delicate equilibrium between the number of homing cells and availability of niches [20,42,43]. Cellular homing to the host BM is mediated by a variety of molecular interactions and is influenced by the phenotype of Askenasy, Farkas 510 the transplanted cells and their stage in the cell cycle [11-16, 19, 42-45].…”
Section: Physiological Considerationsmentioning
confidence: 99%